Isolation of cubic Si3P4 in the form of nanocrystals - Nikiforova, Polina K.; Bubenov, Sergei S.; Platonov, Vadim B.; Kumskov, Andrey S.; Kononov, Nikolay N.; Kuznetsova, Tatyana A.; Dorofeev, Sergey G. (Beilstein Journal of Nanotechnology, 2023)
This article describes an approach for synthesizing silicon phosphide nanoparticles with a defective zinc blende structure under mild conditions through thermal annealing of hydrogenated silicon nanoparticles with red phosphorus. The synthesized Si3P4 nanoparticles were analyzed using FTIR, XRD, electron diffraction, EDX, TEM, Raman spectroscopy, X-ray fluorescence spectrometry, and UV–vis spectrophotometry. For the isolated cubic Si3P4 phase, a cell parameter of a = 5.04 Å was determined, and the bandgap was estimated to be equal to 1.25 eV. Because of the nanoscale dimensions of the obtained Si3P4 nanoparticles, the product may exhibit several exceptional properties as a precursor for diffusion doping of wafers and as anode material for Li-ion batteries. A similar method with a hydrogenation step offers the possibility to obtain other compounds, such as silicon selenides, arsenides, and sulfides.
Keywords: ampoule annealing; defective zinc blende structure; DFT calculations; semiconductor nanocrystals; silicon phosphide